Konstruksi Kelembagaan Perwakilan Dalam Pelaksanaan Asas Kedaulatan Rakyat - Sherlock Halmes Lekipiouw (SASI, 2018)
Constitutionalism is not just a matter of dismantling pairs of texts and their institutions through the constitution, but rather as a leap of critical thinking and concrete actions to provide assurance of social welfare rights as basic rights of citizens who cannot be neglected at all by the organizers of power. That is one way to interpret constitutional theory and law to be more substantive, dignified and grounded for all citizens.